Studies in the Iconography of Blacks in Roman Art - Ako-Adounvo, Gifty (My University, 1999)
The post-Homeric literary sources of the Greek period mention Aioiorec. inhabitants of a distant land, whose physical appearance differs from the Mediterranean somatic norm, but approximates that of peoples referred to in modem times as Black Africans. In the Roman era Aethiopes appear in the literary sources, perceived not only as distant strangers but also as persons familiar to the Roman experience. The sources also mention other peoples: Mauri, Libyes, and Indi, who are distinguished from Aethiopes, but are perceived as having some of the physical characteristics of Aethiopes. An evaluation of the archaeological evidence reveals the methods by which Roman artists conveyed difference from their somatic norm, and the problems they faced in their attempt to portray difference. An INTRODUCTION explains the aims of the thesis and reviews the modem literature. CHAPTER 1 sets out the methodological approach and summarizes ancient literary testimony concerning Greek and Roman perceptions of Blacks. CHAPTER 2 provides an overview of relevant archaeological material of the Greek, Hellenistic, and Roman periods not included in the catalog. CHAPTERS 3, 4, 5, and 6 deal with the iconography of the Black in the Roman period focussing on their appearance in thematic contexts (baths, spectacle, domestic service, and mythology). Following theCONCLUSION, a CATALOGUE lists and describes 56 objects with museum, inventory number, provenience and bibliography. The selected representations date from the Late Hellenistic to the sixth century A.C. They appear in mosaics, sarcophagi, in sculpture, and in paintings from the Mediterranean, Egypt, North Africa, and continental Europe.
Keywords: Roman Art; Iconography